Naratif sebagai Strategi Pembujukan dalam Manifesto Barisan Nasional dalam Pilihan Raya Umum ke-12 Tahun 2008 di Malaysia - Ahmad, Syahruddin Hj Awg (ASPENSI in Bandung, Indonesia, 2008)
ABSTRACT: The Barisan Nasional (BN) manifesto was specially launched for the 12th general election (12 GE) to address the concerns of the people and to ensure that the needs of all Malaysians are being seriously looked into. It was clearly indicated from providing scholarships to children from the needy families to strengthening the police force to enhancing the standard of education, as well developing Chinese new villages and providing assistance to small-and-medium-scale industries. The Barisan manifesto has addressed all the concerns of the people. The manifesto is a guarantee of security, peace and prosperity for all the races. The Barisan track record of service and development is there for all to see. The narrative techniques explicitly applied in BNâs manifesto. It permits voters and grassroots to interpret the political and economy agenda championed by the BN (Barisan Nasional) as ruling party. Voters are able to judge for themselves the candidates and BN on how they speak and communicate with their agenda in such a content. The BNâs manifesto took centre stage as in all other mainstream media. Is the manifesto was merely propaganda or was being set to get an attention from publics? Indeed, the presentation of report card of Ninth Malaysian Plan was objectively drawn peopleâs mind on how government run the business. This paper tries to analyse method and technique of the BNâs campaign in the General Election and responses and judgement of Malaysian voters to it.Key words: the Barisan Nasional manifesto, general election in Malaysia, narrative techniques and votersâ judge.About the Author: Syahruddin Hj. Awg. Ahmad, M.A. ialah Pensyarah pada Program Komunikasi, Sekolah Sains Sosial UMS (Universiti Malaysia Sabah). Beliau menamatkan B.A.Hons dari Universiti Teknologi MARA (UiTM) dalam Mass Communication (Public Relations) tahun 1997; dan M.A. dari Universiti Kebangsaan Malaysia (UKM) dalam Communication (Government Public Relations) tahun 2003. Beliau adalah ahli profesional dalam Institut Perhubungan Raya Malaysia (IPRM); dan bidang pengkhususan penyelidikan beliau adalah Perhubungan Awam (Public Relations and Governmental Public Relations). Bagi urusan sebarang akademik, beliau boleh dihubungi dengan alamat jabatan: Sekolah Sains Sosial (Komunikasi), Universiti Malaysia Sabah (UMS), Beg Berkunci 2073, 88999 Teluk Sepanggar, Kota Kinabalu, Sabah, Malaysia. E-mail: syahag@ums.edu.myHow to cite this article? Ahmad, Syahruddin Hj Awg. (2008). âNaratif sebagai Strategi Pembujukan dalam Manifesto Barisan Nasional dalam Pilihan Raya Umum ke-12 Tahun 2008 di Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.2 [November], pp.391-400. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112.Chronicle of the article: Accepted (June 20, 2008); Revised (September 23, 2008); and Published (November 20, 2008).